The Effect of Digital Finance Usage and Green Awareness on Responsible Consumerism among Students of the Economic Education Study Program at Universitas PGRI Jombang - Bela Purwaning Tyas; Lina Susilowati (Darul Yasin Al Sys, 2026)
The increasing use of digital financial services and the growing importance of environmental awareness have become central factors in shaping responsible consumption behavior among university students. This study aims to analyze the effect of digital finance usage and green awareness on responsible consumerism among students of the Economic Education Study Program at Universitas PGRI Jombang. A quantitative approach with an explanatory research design was employed. The population comprised 107 students from the 2022–2025 cohorts, from which 85 respondents were selected using proportional random sampling. Data were collected through questionnaires and analyzed using multiple linear regression with SPSS version 27. The findings indicate that digital finance usage has a positive and significant effect on responsible consumerism, with a regression coefficient of 0.383 and a significance value of 0.000. Green awareness also has a positive and significant effect, with a regression coefficient of 0.636 and a significance value of 0.000. Simultaneously, digital finance usage and green awareness significantly influence responsible consumerism, as reflected in an Adjusted R Square value of 0.837. The study concludes that effective use of digital financial services and strong environmental awareness encourage more responsible and sustainable consumption behavior among students. These findings contribute to the literature on financial behavior and sustainable consumption by highlighting the combined role of digital finance and green awareness in promoting responsible consumerism, while also implying the need to strengthen digital financial literacy and environmental education in higher education institutions.